E-Commerce and Entrepreneurship (E&E) - Suryanarayana, K. (AMC Indian Journal of Entrepreneurship, 2020)
In todays context, there is a tremendous growth in online technology and there is a major shift in cost, speed, and size. The cost is reduced, speed has increased, and the size has decreased from mainframe computers to hand held devices. This article helps in understanding how this change has improved the usage of technology and the growth of innovative online applications by helping the growth of e-commerce. Various companies have grown across the globe that use online technologies like Amazon, Flipkart, Ola, Uber, Swiggy, Trivago etc. This paper also focuses on these companies and how they were able to use online technologies.